Pathogenesis of experimental salmonid alphavirus infection in vivo: an ultrastructural insight. (December 2016) - Herath, Tharangani; Ferguson, Hugh; Weidmann, Manfred; Bron, James; Thompson, Kimberly; Adams, Alexandra; Muir, Katherine; Richards, Randolph
Abstract Salmonid alphavirus (SAV) is an enveloped, single-stranded, positive sense RNA virus belonging to the familyTogaviridae . It causes economically devastating disease in cultured salmonids. The characteristic features of SAV infection include severe histopathological changes in the heart, pancreas and skeletal muscles of diseased fish. Although the presence of virus has been reported in a wider range of tissues, the mechanisms responsible for viral tissue tropism and for lesion development during the disease are not clearly described or understood. Previously, we have described membrane-dependent morphogenesis of SAV and associated apoptosis-mediated cell death in vitro. The aims of the present study were to explore ultrastructural changes associated with SAV infection in vivo. Cytolytic changes were observed in heart, but not in gill and head-kidney of virus-infected fish, although they still exhibited signs of SAV morphogenesis. Ultrastructural changes associated with virus replication were also noted in leukocytes in the head kidney of virus-infected fish. These results further describe the presence of degenerative lesions in the heart as expected, but not in the gills and in the kidney.